Design and Build A Website-Based Drug Supply Information System (Case Study at Apotek Salam) - Arista Rahmat Ramadhan; Safaruddin Hidayat Al Ikhsan; Berlina Wulandari (Eduvest - Journal of Universal Studies, 2024)
Information technology has an important role in improving the efficiency of services in the health sector, including the management of drug supplies in pharmacies. Apotek Salam faces several obstacles in manual drug stock management, such as lack of stock accuracy, improper inventory counting, and difficulty tracking expired drugs. To overcome this problem, it is necessary to design a website-based drug inventory information system  using PHP and Ajax programming languages as data integration with MySql databases that can display drug stock, price, and expiration date information well. By using  the First Expired First Out (FEFO) method on the website can make it easier to manage stock, ensure that drugs with an approaching expiration date are prioritized, increase efficiency in pharmacy services. In order to get better quality of drug stock with alerts on drug stock that will be yellow and those that have expired in red and stock taking to maintain the quality of drug stock and medical devices at Pharmacy Salam.